LINGUOCULTURAL FEATURES OF SYMMETRY AND ASYMMETRY PHENOMENA IN LITERARY TEXTS OF ENGLISH AND UZBEK LANGUAGES - Azimova Zilola Ismoil qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Introduction A literary text is not merely a source of aesthetic pleasure, but also a profound linguistic  medium  through  which  an  author  conveys  their  worldview,  inner experiences, and cultural values. Literary discourse demonstrates the functional and aesthetic capacities of language, blending the author's unique stylistic choices with culturally embedded expressive means. Artistic language employs a range of rhetorical devices—such as metaphor, simile, parallelism, gradation, and epithet—which enrich the  text's  rhythm,  imagery,  and  emotional  depth.  Among  these,  the  phenomena  of symmetry and asymmetry play a significant role in shaping the internal structure and aesthetic expressiveness of literary works. Analyzing how symmetry and asymmetry manifest  in  English  and  Uzbek  literary  texts  offers  deeper  insight  into  the interconnection  between  language  and  culture,  as  well  as  into  the  aesthetic  and semantic mechanisms that underlie different literary traditions.